Military hospitals through the prism of sociology of architecture - Fedorova, Mariia (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Unlike a painting or a sculpture, architecture, cannot be hidden from the eye of the beholder. Architecture is steadfast and is rarely copied, therefore it truthfully bears information about the function for which it is designed and about the esthetics that are appropriate for the building. Despite closeness of the military system, the architecture of military hospitals reveals a lot about the value, past and present, of the soldier and the doctor, about the attitude towards efficiency and safety, discipline and the organization thereof, and the changes that have taken place in society through the previous 300 years of existence of the hospital system.